1987
DOI: 10.1002/jsfa.2740400210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sulphur dioxide and blanching on the stability of carotenoids of dehydrated carrot

Abstract: The influence of blanching and sulphiting of carrot on the stability of carotenoids of dehydrated carrot was evaluated. The carotenoid content of untreated and treated carrots was measured after dehydration and during storage of dehydrated carrot at 37°C. Sulphiting was found to have a marked effect on the stability of carotenoids of both unblanched and blanched carrots during dehydration and storage at 37°C. The effectiveness of sulphur dioxide was reduced by increasing blanching time to over 1 min, the perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
22
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 18 publications
8
22
0
Order By: Relevance
“…Blanching prior to dehydration of carrots enhanced the stability of carotenoids during storage. This is consistent with the findings of Arya et al (1982), Baloch (1987) and Zhao and Chang (1995).…”
Section: Resultssupporting
confidence: 95%
See 1 more Smart Citation
“…Blanching prior to dehydration of carrots enhanced the stability of carotenoids during storage. This is consistent with the findings of Arya et al (1982), Baloch (1987) and Zhao and Chang (1995).…”
Section: Resultssupporting
confidence: 95%
“…Several researchers have studied the effect of drying on carrot quality (Doymaz, 2004;Lin et al, 1998;Mazza, 1983;Park, 1987;Prakash et al, 2004;Schadle, Burns, & Talley, 1983;Sumnu, Turabi, & Ö ztop, 2005). However, the literature contains few references on the retention of b-carotene and colour stability in dehydrated carrots during storage (Baloch et al, 1973;Baloch, 1987;Negi & Roy, 2001). Kinetic parameters including reaction order, rate constant and activation energy are essential to predict the quality of foods.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced rate of carotenoids destruction in sulphite treated carrot was reported by Arya et al (1979) and Zhao and Chang (1995). Baloch et al (1987) also reported that SO 2 showed a protective effect on the carotenoids of the blanched carrot and effectiveness of SO 2 increased with increase in SO 2 content. There was a significant (p≤0.05) reduction in the β-carotene content of carrot slices during storage.…”
Section: Resultssupporting
confidence: 57%
“…Baloch et al (1981) found that dipping in solution of sodium bisulfite improved the reconstitution of the dried carrots. Rehydration ratio was more in dried slices packed in AFL pouches as compared to those packed in HDPE pouches due to less moisture content in product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation